Phytogenic Synthesis and Characterization of NiO-ZnO Nanocomposite for the Photodegradation of Brilliant Green and 4-Nitrophenol. (13th October 2021) - Haq, Sirajul; Raja, Aqsa Waheed; Rehman, Sadiq Ur; Mezni, Amine; Ben Ali, Manel; Hedfi, Amor; Shahzad, Muhammad Imran; Rehman, Wajid; Shahzad, Nadia; Waseem, Muhammad; Ahmad, Pervaiz
Abstract : The NiO-ZnO nanocomposite (NiO-ZnO NC) was synthesized by ecofriendly process by using Diospyros kaki ( D. kaki ) extract of leaves as reducing and capping agents. X-ray diffraction (XRD) was used for examined crystallinity, cell dimensions, and crystallite size (7.6 nm). To determine the purity of sample and weight percentage, energy dispersive X-ray (EDX) is used. The surface morphology was determined by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). By using Fourier transform infrared spectroscopy (FTIR), functional groups in samples were determined. By using diffuse reflectance data (DRS), band gap energy calculated via Tauc plot was 3.23 eV. The photocatalytic activity was checked against brilliant green (BG) and 4-nitrophenol (4-NP) and 92.5% and 69.7% of brilliant green (BG) and 4-nitrophenol (4-NP) were degraded with rate of degradation which were 0.0281 and 0.011 min −1 .